2016
DOI: 10.3389/fmicb.2016.01877
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Metabolism via the Entner-Doudoroff Pathway in Campylobacter: A Rare Trait that Enhances Survival and Promotes Biofilm Formation in Some Isolates

Abstract: Isolates of the zoonotic pathogen Campylobacter are generally considered to be unable to metabolize glucose due to lack of key glycolytic enzymes. However, the Entner-Doudoroff (ED) pathway has been identified in Campylobacter jejuni subsp. doylei and a few C. coli isolates. A systematic search for ED pathway genes in a wide range of Campylobacter isolates and in the C. jejuni/coli PubMLST database revealed that 1.7% of >6,000 genomes encoded a complete ED pathway, including both C. jejuni and C. coli from div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 63 publications
1
29
0
Order By: Relevance
“…Furthermore, C. concisus does not have genes for the ED pathway or for fucose catabolism, unlike as documented in certain C. jejuni strains ( Fig. 1 and Additional file 1: Table S1 and Additional file 5: Table S5) [38]. Collectively, these findings support the previous characterization of C. concisus as non-saccharolytic [1].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Furthermore, C. concisus does not have genes for the ED pathway or for fucose catabolism, unlike as documented in certain C. jejuni strains ( Fig. 1 and Additional file 1: Table S1 and Additional file 5: Table S5) [38]. Collectively, these findings support the previous characterization of C. concisus as non-saccharolytic [1].…”
Section: Discussionsupporting
confidence: 82%
“…doylei 269.97 (NC_009707.1) and not found in most C. jejuni subsp. jejuni strains [38]. In addition, the tetrathionate reductase genes tsdA (C8J_0815) and the tsdA paralog (C8J_0040) were discovered in C. jejuni strain 81116 [50].…”
Section: The Reference Genes Used To Identify Similar Genes and Protementioning
confidence: 99%
See 1 more Smart Citation
“…However, the adaptation present in the aerotolerant C. coli OR 12 also enables aerobic growth on CCDA. Modifications to central metabolism are emerging amongst campylobacters, for example it was recently reported that 1.7% of thermophilic campylobacters have the potential to metabolize glucose via the Entner-Doudoroff pathway (Vegge et al, 2016). This pathway also permits the metabolism of L -fucose, which has been reported to provide a competitive advantage to C. jejuni in a piglet colonization model (Stahl et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…2-keto-3-deoxy-6-phosphogluconate (KDPG) is the key metabolite of the Entner-Doudoroff (ED) pathway -also known as the KDPG pathway -which is estimated to be utilized by 27% of the heterotrophic prokaryotic microorganisms for sugar and sugar acid (e.g., gluconate) degradation and has recently been found to play also a significant role in cyanobacteria, algae and even higher plants (Flamholz et al, 2013;Chen et al, 2016). Among the ED pathway utilizing organisms there are numerous human pathogens like Escherichia coli, Salmonella enterica, Neisseria gonorrhoeae, Klebsiella pneumoniae, Helicobacter pylori, Pseudomonas aeruginosa, Legionella pneumophila, Campylobacter spp., and Pasteurella pestis (Patra et al, 2012;Vegge et al, 2016;Gonzalez-Mula et al, 2019). In addition, several plant pathogens like Xanthomonas campestris, Pectobacterium carotovorum, Agrobacterium tumefaciens and other organisms of agricultural importance, like Rhizobiaceae, as well as some organisms of biotechnological interest like e.g., Zymomonas mobilis, Gluconobacter oxydans, are ED pathway utilizers (Stowers, 1985;Richhardt et al, 2012;He et al, 2014).…”
Section: Introductionmentioning
confidence: 99%